ANALISIS SELF EFFICACY MAHASISWA MELALUI KEMAMPUAN PRESENTASI DI KELAS - Hernawati, Diana; Amin, Mohamad (Universitas Nahdatul Ulama Surabaya, 2017)
Presentation is one of the communication skills enabling the speakers to be able to think logically, accurately and firmly. This study was aimed at analyzing the students’ selfefficacy through their classroom presentations. The analysis was anchored on the empirical data obtained through observation results of 160 participants coming from the Biology Education Department, Siliwangi University, Tasikmalaya. In addition, the obtained data were analyzed and computed with descriptive statistical framework. The findings generally revealed that the students were accustomed to performing classroom presentations. This was supported by the evidence showing that the efficiency and effectiveness of classroom presentations were under 75% percentages of the total averages. Besides, the problem discussions were conducted with theoretical, practical, rationalistic and responsible attitudes, particularly under 75% percentages of the total averages. Also, the classroom presentations ran bi-directionally beyond 75% percentages of the total averages. Likewise, each member of presenters was actively engaged in classroom presentations with 75% percentages beyond the total averages. Additionally, the ability to present the materials attractively (e.g. videos, diagrams, pictures, etc.) was still under 75% percentages of the total averages. For these reasons, the students were accustomed to presenting the learning materials in the classrooms represented by their well-established presentation skills. However, a few skills should be taken into account through intensive trainings because they were still under the expected results.